Assessment and valuation of government policies to improve food animal welfare - Richard Bennett; Kelvin Balcombe; Heather Maggs; Siobhan Abeyesinghe; Gareth Arnott; Nick Bell; Andrew Butterworth; Jennifer Duncan; Cathy Dwyer; Marie Haskell; Fritha Langford; Siobhan Mullan; et al. (Food Policy, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Adopted “mammoths” from Alaska turn out to be a whale's tale - Matthew J. Wooller; Pat Drukenmiller; Gonzalo Oteo‐García; Francesca Di Paolo; Love Dalén; Nick Baker; Nancy Bigelow; Stormy Fields; Sambit Ghosh; Kathryn E. Krasinski; Ben Lamm; Alistair J. Monteath; et al. (Journal of Quaternary Science, 2026)
Radiocarbon‐dated fossils indicate woolly mammoths were extirpated from mainland Beringia around 13 000 years ago. However, environmental DNA in permafrost suggests small “cryptic“ populations survived into the Holocene. Resolving this discrepancy is crucial to understanding the drivers of mammoth extinction. The Adopt‐a‐Mammoth project, launched in 2022, is increasing the number of radiocarbon‐dated mammoth fossils to locate the chronologically youngest specimens. Here, we report results from two “mammoth“ vertebral epiphyseal plates from interior Alaska that produced the youngest radiocarbon ages associated with mammoth specimens (~1900–2700 cal a BP). However, isotopic data indicated that these individuals consumed marine resources, and subsequent ancient DNA analysis revealed the specimens were in fact from a North Pacific Right whale and a Minke whale. Solving the mystery of recent “mammoth” fossils raised new questions. How did the remains of ancient whales become emplaced in sediment so far from the coastline? We briefly consider four scenarios to account for this.

Variability in surface CO2 flux: Implication for monitoring surface emission from geothermal fields - Tsung-Han Jimmy Yang; Isabelle Chambefort; Michael Rowe; Agnes Mazot; Anya Seward; Cynthia Werner; Tobias Fischer; Jun Seastres; Farrell Siega; Nick Macdonald; Thomas Brakenrig; Lauren Coup; et al. (Geothermics, 2024)

Understanding caldera degassing from a detailed investigation at Lake Rotoiti, Okataina Volcanic Centre, New Zealand - Tsung-Han Jimmy Yang; Isabelle Chambefort; Agnes Mazot; Michael C. Rowe; Brad Scott; Nick Macdonald; Cynthia Werner; Tobias P. Fischer; Cornel E.J. de Ronde (Journal of Volcanology and Geothermal Research, 2023)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Present trans‐Pacific disjunct distribution of A ristolochia subgenus I sotrema ( A ristolochiaceae) was shaped by dispersal, vicariance and extinction - Favio González; Sarah T. Wagner; Karsten Salomo; Lars Symmank; Marie‐Stéphanie Samain; Sandrine Isnard; Nick P. Rowe; Christoph Neinhuis; Stefan Wanke (Journal of Biogeography, 2014)
Aim I sotrema is a monophyletic subgenus of A ristolochia with species in E ast A sia and N orth/ C entral A merica. Earlier studies, based on limited sampling, suggested that the A sian and A merican species do not form two reciprocal sister clades. We reconstructed phylogenetic relationships within I sotrema to infer the biogeographical events that have shaped its present‐day distribution. Location E astern A sia, N orth A merica, M exico, C entral A merica. Methods We performed parsimony and Bayesian phylogenetic analyses of 54 accessions using three chloroplast regions. The temporal origins were traced with relaxed phylogenetics and penalized likelihood using fossil calibrations; these methods were combined with ancestral area reconstructions in a comparative approach using statistical dispersal–vicariance analysis ( S‐DIVA ) and dispersal–extinction–cladogenesis ( DEC ) analyses. Results The ancestors of the herbaceous eastern N orth A merican species and the woody species probably diverged during the O ligocene. The woody species form a Neotropical and a N orth A merican/ E astern A sian clade. Diversification in the Neotropical and N orth A merican/ E astern A sian clades occurred mostly in the M iocene. In the latter clade, two further intercontinental splits are reconstructed: between the exclusively western N orth A merican A ristolochia californica and most of the A sian taxa, and between A . manshuriensis and A . tomentosa . Main conclusions The present distribution of I sotrema developed via a number of dispersal, vicariance and extinction events. The disjunct distributions observed may be the result mainly of non‐synchronous events (e.g. a decrease of mean annual temperature in the O ligocene and the development of unfavourable conditions across the B ering land bridge) that were responsible for the fragmentation of the mesophytic forests. Later diversifications may be correlated with events such as the orogeny of the W estern C ordillera and A ppalachian M ountains, the development of extensive grasslands in N orth A merica, and the mainland extension of C entral A merica southwards to western and central P anama.

Development and Growth Form of the Neotropical Liana Croton nuntians: The Effect of Light and Mode of Attachment on the Biomechanics of the Stem - Friederike Gallenmller; Nick Rowe; Thomas Speck (Journal of Plant Growth Regulation, 2004)

Diversity of Mechanical Architectures in Climbing Plants: An Evolutionary Perspective - Nick Rowe; Sandrine Isnard; Thomas Speck (Journal of Plant Growth Regulation, 2004)